Decreased Susceptibility of Shigella Isolates to Azithromycin in Children in Tehran, Iran - Parisa Behruznia; Mehrzad Sadredinamin; Ali Hashemi; Bahareh Hajikhani; Neda Yousefi Nojookambari; Mahboobeh Behruznia; Zohreh Ghalavand (Canadian Journal of Infectious Diseases and Medical Microbiology)
Azithromycin (AZT) has widely been used for the treatment of shigellosis in children. Recent studies showed a high rate of decreased susceptibility to azithromycin due to different mechanisms of resistance in Shigella isolates. Accordingly, the purpose of this study was to investigate the role of azithromycin resistance mechanisms of Shigella isolates in Iran during a two-year period. In this study, we investigated the mechanisms of resistance among Shigella spp. that were isolated from children with shigellosis. The minimum inhibitory concentration (MIC) of Shigella isolates to azithromycin was determined by the agar dilution method in the presence and absence of Phe-Arg-β-naphthylamide inhibitor. The presence of 12 macrolide resistance genes was investigated for all isolates by PCR for the first time in Tehran province in Iran. Among the 120 Shigella spp., only the mph(A) gene (49.2%) was detected and other macrolide resistance genes were absent. The phenotypic activity of efflux pump was observed in 1.9% of isolates which were associated with over expression of both omp(A) and omp(W) genes. The high prevalence of the mph(A) gene among DSA isolates may indicate that azithromycin resistance has evolved as a result of antimicrobial selection pressures and inappropriate use of azithromycin.